Preventive and conservative prosthodontic treatment using overdenture and Richmond crown - Jevin S. Cialy; Bahruddin Thalib; Mohammad Dharmautama; Wahipa Wiro; Ervina Ervina (Journal of Dentomaxillofacial Science, 2016)
Prosthodontic treatment aims to restore the chewing function (rehabilitation) and to prevent tooth decay and bone resorption (preventive and conservative). As an example, treatment by overdenture and Richmond crown. Overdenture is a partial or complete removable denture covered and supported by one or more teeth, the tooth roots and/or dental implants. Richmond crown is fixed denture by post and crown system, in which the post part goes into the root canal and its crown covers the entire of original tooth crown surface. By retaining the original teeth and/or roots, it could improve the stability and retention of the denture, and defend proprioseptic of teeth and vertical dimensions. To provide information about preventive prosthodontic treatment and prevention by using overdenture and Richmond crown. Case Report: A 50 year old woman only has 44 teeth on the mandible which is indicated for the overdenture construction and loss teeth 13, 14, 17 and 27 on the maxilla with deep caries in teeth 22 which is indicated for a removable partial denture (RPDs) construction by Richmond crown gear 22. On an early stage study, printing models is done. Then treatment of the root canal on teeth 22 and 44, followed by root canal preparation, core construction (cast post) and Richmond crown on tooth 22 and bareroot preparation on tooth 44 for overdenture construction. The procedure followed by printing, recording bite to insertion. Choosing treatment either overdenture or Richmond crown is very important because it could mantain remain original teeth, thus it can help to improve the retention and stabilization.